METHODOLOGICAL APPROACH TO THE NOUN GENDER AND NUMBER CATEGORIES IN TEXTBOOK FOR THE SECOND GRADE OF ELEMENTARY SCHOOL - Vesic, Ljubica; Mitrović, Milena (Metodička teorija i praksa, 2025)
Given that the gender and number of nouns are adopted for the first time in the second grade of elementary school in Republic of Serbia. The subject of this research is the way of processing these grammatical categories at the age when the concepts of noun gender and number are introduced and when basic linguistic rules are established. To examine the current solutions, we analyzed eleven approved textbooks for the second grade of elementary school. We considered the starting texts, the provided examples, linguistic accuracy, and methodological gradualness, as well as the possibilities for improving grammar teaching. The research results show that: 1) there are different ways of introducing the concept of gender and number of nouns to students; 2) the introduction of grammatical gender through the concept of natural gender dominates in the second-grade textbooks; 3) there are numerous places that cause linguistic confusion or represent a kind of methodological trap. We believe that these inaccuracies can lead to significant challenges in teaching grammar in the higher grades of elementary school. In the conclusion of the paper, concrete steps are proposed in the concluding part of the paper for the introduction of the concept of gender and number of nouns in the second grade of elementary school.
Keywords: curriculum; Serbian language teaching; grammar teaching; textbook; gender of nouns and number nouns